Entre texte et image : réflexions sur la traduction des titres de tableaux de Paul Gauguin - Walkiewicz, Barbara (Studia Romanica Posnaniensia, 2021)
The aim of this article is to analyse the translation strategies used to translate Paul Gauguin’s painting titles from Tahitian and French to Polish. We will analyse the titles that the artist painted directly on the canvases by making them invariant just like the image itself. The translations analysed come from works on Gauguin’s art and Impressionism, published in Polish since the 1960s of the 20th century.